Overexpression of ADAM10 in oral squamous cell carcinoma with metastases - Stasikowska-Kanicka, Olga; Wągrowska-Danilewicz, Małgorzata; Kulicka, Paulina; Danilewicz, Marian (Polish Journal of Pathology, 2018)
ADAMs (a disintegrin and metalloproteinase) are important mediators of cell signalling events, which play a role in the pathogenesis and progression of cancers. Immunohistochemical method was used to examine the immunoexpression of ADAM10 and microvessel density in 80 cases of oral squamous cell carcinoma (OSCC): without metastases – OSCC M(–) (n = 38), and with metastases – OSCC M(+) (n = 42), in 24 cases of oral leukoplakia (OLK), (15 cases with low-grade dysplasia – OLK-LG, and 9 cases with high-grade dysplasia – OLK-HG), and 19 controls. The immunoexpression of ADAM10 and the mean number of vessels were significantly increased in both groups of OSCC in comparison to both groups of OLK and controls. Moreover, the immunoexpression of ADAM10 and microvessel density were significantly increased in the OSCC M(+) group in comparison to the OSCC M(–) group. No statistically significant differences were found between immunoexpression of ADAM10 and microvessels density in the OLK-LG, OLK-HG, and control cases. In conclusion, the present study revealed overexpression of ADAM10 in OSCCs, especially in OSCC with metastasis. These findings suggest that ADAM10 could potentially contribute to metastases of oral cancer. Although, our findings suggest that ADAM10 may be involved in angiogenesis of OSCC, further studies are required to determine the role of ADAM10 in this process.